Evaluation on the employment profile and graduates’ perception on employability among biomedical science graduates from 2016-2019 of International Islamic University Malaysia (IIUM) - Mat Rohim, Muhammad ‘Ammar; Ramli, Norazsida; Mohamad, Mardhiah (IIUM Press, 2025)
Background: The employment rate among fresh graduates in Malaysia, particularly Biomedical Science graduates, has become a major concern. This survey was conducted to assist the Biomedical Science Education Provider (BSEP) at the International Islamic University Malaysia (IIUM) in tracking alumni employment profiles and gathering feedback for improving learning and teaching activities. The insights gained from this survey will enable the Academic Education Provider (AEP) to evaluate educational outcomes, contributing to the continuous enhancement of biomedical science education standards. Methods: An online questionnaire was used as the primary tool for data collection. The questionnaire assessed graduates' job profiles, perceptions of how their education and training aligned with their current employment, and included a section for additional comments and suggestions. A total of 92 graduates (38.3% response rate) from a pool of 240 Biomedical Science alumni participated in this study. Results: Findings indicated that 69.6% (n=64) of respondents were employed, 10.9% (n=10) were unemployed, and 19.6% (n=18) were outside the labour force, with 17 of these pursuing further studies. A significant association was found between curriculum score and employment status (p=0.029, Phi=0.317). However, no significant associations were observed between academic performance or year of graduation and employment status. Conclusions: In conclusion, the majority of IIUM Biomedical Science graduates benefited from the knowledge and training provided during their studies. The comments and suggestions collected through this survey will be used to inform and strengthen the next curriculum review.